Social Environment of Friends, Family, Communities, and HIV/AIDS Cases - Indri Lestari; Dyah Wulan Sumekar Rengganis Wardani; Jhons Fatriyadi Suwandi; Samsul Bakri (Universitas Muhammadiyah Yogyakarta, 2022)
Control of HIV/AIDS infection can be done by screening at-risk groups in the social environment to prevent transmission. This study aims to determine the social environment of friends, family, and society’s influence on HIV/AIDS incidence. The study was conducted in December 2020–January 2021 at six Bandar Lampung health centers. The 111 respondents were divided into case/reactive and control/non-reactive groups, with a 1:2 ratio (37:74). Data were obtained by interview. The independent variables were the social environment of friends, family, and community, while the dependent variable was HIV/AIDS incidence. The data were analyzed bivariate and multivariate with the Binary Logistics Regression test utilizing Minitab 16 application, with CI 90% and α 0.1 significance level. The results showed that friends with HIV’s social environment had p 0.087; friend's education p 0.542; risky behavior from friends p 0.853; friends with risky behavior p 0,172; HIV family social environment p 0.999; family education p 0.999; risky behavior from family p 0.998; families with risky behavior p 0.999; HIV community social environment p 0.999; public education p 0.330; risk behavior from the community p 0.690; community with risky behavior p 0.862. Thus, only friends with HIV’s social environment affected HIV/AIDS incidence. Furthermore, having friends with HIV’s social environment will increase the risk of getting HIV/AIDS.